Medications associated with weight gain - Malone, Margaret (The Annals of pharmacotherapy, 2005)
To review available literature regarding weight gain associated with commonly prescribed drugs and adjunctive therapy used to limit weight gain. Information was retrieved from a MEDLINE English-literature search between 1995 and July 2005, with a major subject heading of weight gain/drug effects excluding complementary alternative medicines. Other limits applied included human subjects and individuals >19 years of age. Additionally, references from retrieved articles were reviewed to identify other literature sources. Changes in weight are generally reported as a primary or secondary outcome of many studies. Where possible, prospective, randomized, controlled trials were preferred; however, many studies were retrospective or open label. Meta-analyses and recent reviews, especially those providing a detailed description of the proposed mechanism involved in weight gain beyond the scope of this article, were included. Limited information was available from case reports. Studies were categorized by therapeutic area including psychiatry, neurology, diabetes, and other miscellaneous drug therapy. Medications used to intentionally stimulate appetite for weight gain, such as megesterol acetate, were not included. Weight gain with medication is usually associated with individual agents within a class. The tendency to cause weight gain is often related to differential specificity and sensitivity of binding to receptors involved with appetite regulation. Clinically significant weight gain is associated with some commonly prescribed medicines. There is wide interindividual variation in response and variation of the degree of weight gain within drug classes. Where possible, alternative therapy should be selected, especially for individuals predisposed to overweight and obesity.